2014
DOI: 10.1186/1472-6874-14-28
|View full text |Cite
|
Sign up to set email alerts
|

Women’s values in contraceptive choice: a systematic review of relevant attributes included in decision aids

Abstract: BackgroundWomen can choose from a range of contraceptive methods that differ in important ways. Inadequate decision support may lead them to select a method that poorly fits their circumstances, leading to dissatisfaction, misuse, or nonuse. Decision support interventions, such as decision aids, may help women choose a method of contraception that best fits their personal circumstances. To guide future decision aid development, we aim to summarize the attributes of contraceptive methods included in available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 34 publications
0
56
0
4
Order By: Relevance
“…This patient-informed process is consistent with recommendations to include users in the development of decision aids to achieve a more patient-centered intervention. (38) The tool was enthusiastically received by patients and results from the pilot evaluation revealed trends towards better outcomes with use of the tool, including higher satisfaction with method choice and increased reports of any knowledge about LARC methods among women who had no previous knowledge. The increased knowledge about LARC methods among patients who used the tool was particularly encouraging given that we have designed the educational component of the intervention to be self-motivated, in that it does not automatically direct users to review all of the information provided for each method.…”
Section: Discussionmentioning
confidence: 99%
“…This patient-informed process is consistent with recommendations to include users in the development of decision aids to achieve a more patient-centered intervention. (38) The tool was enthusiastically received by patients and results from the pilot evaluation revealed trends towards better outcomes with use of the tool, including higher satisfaction with method choice and increased reports of any knowledge about LARC methods among women who had no previous knowledge. The increased knowledge about LARC methods among patients who used the tool was particularly encouraging given that we have designed the educational component of the intervention to be self-motivated, in that it does not automatically direct users to review all of the information provided for each method.…”
Section: Discussionmentioning
confidence: 99%
“…However, these also, either explicitly or implicitly, privilege effectiveness over women's preferences for other method characteristics [55,56]. In addition, a systematic review of decision aids for contraceptive methods developed between 1985 and 2013 found that the contraceptive attributes important to women were inconsistently included in decision aids [57]. Overall, these findings indicate the importance of future decision aids to be informed by a patient-centered framework by including and prioritizing individual women's preferences in their choice of a contraceptive method.…”
Section: Interventions To Datementioning
confidence: 98%
“…2009; Wyatt et al. 2014). The major strands of evidence on factors that influence method choice fall into the following categories: information, availability, access, and affordability (Tsui and Ochoa 1992; Korachais et al.…”
Section: Introductionmentioning
confidence: 99%